KONTRIBUSI PERSEPSI SISWA TENTANG KOMPETENSI PROFESIONALISME GURU DAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR MATA PELAJARAN DASAR LISTRIK ELEKTRONIKA KELAS X JURUSAN TEKNIK ELEKTRONIKA SMK NEGERI 5 PADANG - Adi Tiawarman; Nelda Azhar; Hanesman Hanesman (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
Abstract The purpose of this study to reveal the contribution of teachers' professional competence and creativity of students jointly or individually on learning outcomes. The population of this study amounted to 92 peoples and the sample totaled 48 peoples. Random sampling technique (Simple Random Sampling). The data was taken from the results of the student learning of subject teachers Basic Electrical Electronics, data professional competence of teachers and creativity of students were collected through  questionnaires that were distributed to the students. Data were considered to meet the assumptions and requirements analysis, results showed that (1) the professional competence of teacher and creativity of students jointly contribute significantly to the learning outcomes of 38.57%, (2) the professional competence of teachers contribute significantly to the learning outcomes of 16.4%, (3) creativity of students contribute significantly to the learning outcomes of 12.5 %. It can be concluded that the professional competence of teacher and creativity of students jointly and individually contribute to the learning outcomes. Key Word : Student Perceptions About Professional Competence Teacher, Creativity Student, Learning Outcomes.